Looking back from the medium term - the European Capital of Culture project of Pecs, as shown by public opinion polls - Koltai, Zoltan (Civilia, 2013)
What has actually remained of the first European Capital of Culture (ECOC) programme in Hungary? Is it really another bad example for incompetence and another failure story of money spent in an intransparent way or shall we agree with those who consider the Pecs ECOC programme as a success story, talking of a motorway built, high quality events, new facilities of international standard and a city made more liveable? Is it meaningful, anyway, to make an accurate balance only after just more than two years following the programme year? Short term balances can surely be made. Does it make sense to talk about a clear success or failure? I do not think it does.The publication of our research findings may put a different light on the professional views, by introducing the results of a questionnaire survey done with the inhabitants.The expectations of the population stated in 2008 were met, the series of events still lives as a positive experience in the majority of the respondents, and so the judgement of Pecs has changed for the better both locally and nationally, and also in the international arena. The key projects seem to be viable; numbers of visitors to the newly established cultural institutions are far above the values defined in the project expectations.The present essay is an attempt, partly based on the author's own empirical survey based on questioning more than three thousands respondents in Hungary between 2008 and 2012.
Keywords: European Capital of Culture; Expectations; Willing to participate; Key projects; The image of the city; Pecs